1995
DOI: 10.1084/jem.182.2.531
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of multiple peptide cores by a single T cell receptor.

Abstract: SummaryWe present evidence that a single T cell clone can recognize at least five different overlapping peptides, each with its distinct core structure, in the context of the same major histocompatibility complex (MHC) molecule. Distinct core residues are crucial for triggering the T cell receptor (TCR) in each case. These results suggest that the TCR (a) has multiple sets of contact residues for alternative peptide-MHC ligands, the binding to any one of which can trigger the cell; and/or (b) is able to attach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 29 publications
2
36
2
Order By: Relevance
“…Kinetic and thermodynamic studies also provide evidence that the TCR and/or peptide-MHC have flexible binding surfaces that stabilized upon binding and suggest that conformational flexibility may contribute to cross-reactivity in Ag recognition, as observed in the present study (45). On the other hand, in a study in which a single T cell clone could recognize at least five different peptides, it was suggested that the TCR may have multiple sets of contact residues for different peptide/MHC ligands, binding to any one of which can trigger the cell, and/or that the TCR could interact with the peptide/MHC complex in more than one orientation (9). It is therefore likely that several peptide sequences may satisfy the requirements of TCR recognition once they have crossed the hurdle of MHC binding with appropriate affinity.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Kinetic and thermodynamic studies also provide evidence that the TCR and/or peptide-MHC have flexible binding surfaces that stabilized upon binding and suggest that conformational flexibility may contribute to cross-reactivity in Ag recognition, as observed in the present study (45). On the other hand, in a study in which a single T cell clone could recognize at least five different peptides, it was suggested that the TCR may have multiple sets of contact residues for different peptide/MHC ligands, binding to any one of which can trigger the cell, and/or that the TCR could interact with the peptide/MHC complex in more than one orientation (9). It is therefore likely that several peptide sequences may satisfy the requirements of TCR recognition once they have crossed the hurdle of MHC binding with appropriate affinity.…”
Section: Discussionmentioning
confidence: 71%
“…Similarly, while eight identical residues were required in the recognition of a human HLA-DQ-restricted clone by two different T cell epitopes from mycobacterial heat shock protein 65 and the human heat shock protein 60 (35), only two unique residues were sufficient for the recognition of an HLA-DR1-restricted T cell clone by a peptide from the influenza virus hemagglutinin (36). Extreme cases of T cell cross-reactivity involving peptides without any apparent sequence homology have also been recently reported (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)37). For example, Bharadwaj et al observed degenerate recognition of a chimeric peptide based on MBP by cloned T cells (2).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…On the other hand, it is also possible that a single peptide containing multiple anchors might bind a single MHC class II allele with distinct registers and thus generate different antigenic MHC class II-peptide conformers, each recognized by a specific set of TCR [20,22,45].…”
Section: Discussionmentioning
confidence: 99%
“…As described by James et al [44], promiscuous peptides that bear different anchors were found to contain multiple epitopes, each binding in a monogamous way a specific HLA-DR allele. Therefore, these peptides do not represent real promiscuous epitopes, but rather a linear array of different monogamous epitopes.On the other hand, it is also possible that a single peptide containing multiple anchors might bind a single MHC class II allele with distinct registers and thus generate different antigenic MHC class II-peptide conformers, each recognized by a specific set of TCR [20,22,45].In line with this observation, our data are consistent with the possibility that the MAGE-A3-derived p57 and p58 peptides, which are predicted to contain different putative P1 anchors for the HLA-DR Ã 1101 allele, bind into the HLA-DR groove in different registers, generating different peptide-HLA-DR conformers. By reducing the number of putative anchor residues predicted in the promiscuous peptides, therefore minimizing the number of different registers that the peptide can assume into the MHC class II groove, we show that it is possible to generate functional HLA-DR Ã 1101 tetramers that bind the specific TCR.…”
mentioning
confidence: 99%